Going rogue : [large type] rise and shine twenty-nine - Evanovich, Janet (Evanovich, Janet. Stephanie Plum novel, 2022)
"Stephanie Plum knows something is amiss when she turns up for work at Vinnie's Bail Bonds to find longtime office manager Connie Rosolli hasn't shown up. Stephanie's worst fears are confirmed when she gets a call from Connie's abductor, who only release her in exchange for a mysterious coin that a recently murdered man left as collateral for his bail. Unfortunately, this coin is nowhere to be found. Stephanie will require the help of her Grandma Mazur, best pal Lula, boyfriend Morelli and hunky security expert Ranger to find the coin, learn its value, and save Connie. As they get closer to unraveling the reasons behind Connie's kidnapping, her captor grows more threatening, and soon Stephanie has no choice but to throw caution to the wind, follow her instincts, and go rogue"--